2009
DOI: 10.5016/1806-8774.2009v11p21
|View full text |Cite
|
Sign up to set email alerts
|

<b>Biological Effects of Myristica fragrans</b>

Abstract: Jaiswal P, Kumar P, Singh VK, Singh DK. Biological Effects of Myristica fragrans. Annu Rev Biomed Sci 2009;11:21-29. Myristica fragrans is an evergreen tree that produces two spices, nutmeg and mace. Its medicinal uses in the aurvedic system of treatment are based on traditional experience inherited from one generation to other. Scientists from various disciplines are now directing their research towards investigating the effects of M. fragrans on human health. The chemical constituents of M. fragrans have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…Previous research has confirmed the presence of neolignans, lignans, phenylpropanoids, flavonoids, esters, and phenolic constituents [73][74][75][76][77] in the aqueous and organic solvent extracts of mace. Mace oils have also shown the presence of several terpenes, and its derivatives [78]. All the compounds referenced above have demonstrated a broad spectrum of antimicrobial activity.…”
Section: Antibacterial Activity Of Aqueous Extracts and Agnps Synthesized From Macementioning
confidence: 96%
“…Previous research has confirmed the presence of neolignans, lignans, phenylpropanoids, flavonoids, esters, and phenolic constituents [73][74][75][76][77] in the aqueous and organic solvent extracts of mace. Mace oils have also shown the presence of several terpenes, and its derivatives [78]. All the compounds referenced above have demonstrated a broad spectrum of antimicrobial activity.…”
Section: Antibacterial Activity Of Aqueous Extracts and Agnps Synthesized From Macementioning
confidence: 96%
“…In addition to the high concentration in this seed, myristicin can also be found in cinnamon, parsley, some types of pepper and other spices native to Asia. Nutmeg was used in ancient times (in India and other regions of Asia) to treat anxiety, stomach cramps, nausea and diarrhea [7]. In addition, it has been described as a food preservative, as it has antimicrobial activities, and it is currently used as a flavoring agent by the food industry [8].…”
Section: Introductionmentioning
confidence: 99%
“…When used in very high amounts, myristicin can have toxic effects, leading to liver degeneration and mental confusion, as it is toxic to the central nervous system. It is believed that myristicin is in the main responsible for the benefits described with the use of nutmeg, as well as for its toxic effects, since it is the largest compound present in this spice [7].…”
Section: Introductionmentioning
confidence: 99%
“…Miristisin, -pinen, safrol, dan sabinen sudah lama diketahui sebagai bioaktif antiseptik seperti antimicrobial dan antibacterial (Nurdjannah 2007;Li and Yang 2012;Zhang et al 2014). Senyawa-senyawa tersebut juga berkhasiat sebagai antidiare (Grover et al 2002), antiperadangan (Asgarpanah and Kazemivash, 2012), antikanker (Olajide et al 1999), antioksidan untuk melawan toksisitas bromat pada jaringan ginjal (Gupta et al 2013;Oseni et al 2015), antidepresi (Moinuddin et al 2010), dan analgesik/pereda nyeri (Beckerman dan Persaud 2019).…”
Section: Peluangunclassified